Television use and family mealtimes among a sample of US families with preschoolers. Issue 1 (2nd January 2018) - Wenhold, Halie; Harrison, Kristen
Abstract: Research has connected family mealtimes with nutrition, child development, and child academic performance. However, it is not clear how television is associated with the quality of family mealtimes, especially mealtime ritualization (MR), mealtime harmony (MH), and child food intake. Parents of preschoolers ( N  = 278, average age 40–76 months) completed questionnaire measures of television use, MR, MH, and dietary intake. Controlling familial demographics, television use during meals was a significant predictor of less MR and preschooler fruit and vegetable intake, but not of MH. Additionally, a three-way interaction between mealtime television use, MR, and MH visualized differing patterns of mean preschooler obesogenic food intake among families with low and high TV mealtime use. Discussion focuses on the importance of continuing to investigate the impact of screen media use on family mealtimes and other rituals related to child health.